Martial arts fun - Meister, Cari (Sports fun., 2021)
"Martial Arts are thrilling to watch, but they're even more fun to do! Kids can take part in the sport by learning what martial arts are, what gear and skills are needed, what happens during lessons, and how to be a good sport. A skill-building activity helps kids participate in the fun"--